The era of Chinese multinationals : competing for global dominance - Casanova, Lourdes, ....-; Miroux, Anne, ....- (London : Academic Press / Elsevier, 2020)
Chinese multinationals have grown in size and increased their global presence dramatically over the last decade. They have emerged as formidable competitors for western incumbents. These firms have instigated profound changes, such as displaced trade and investment flows, new business models, and the emergence of a new geography of global innovation. In a single volume, The Era of Chinese Multinationals captures the forces driving the disruptive growth of Chinese multinational corporations. Following a presentation of the surge of Chinese companies, the book turns to corporate characteristics of those firms and how they compare with western multinationals in terms of revenues, profits, branding, and business strategy. The book uses data and case studies to depict the relevant issues with the goal of providing insights to global executives on collaborating and competing with Chinese companies.